2019
DOI: 10.1002/jms.4430
|View full text |Cite
|
Sign up to set email alerts
|

Formation and hydrolysis of gas‐phase [UO2(R)]+: R═CH3, CH2CH3, CH═CH2, and C6H5

Abstract: The goals of the present study were (a) to create positively charged organo-uranyl complexes with general formula [UO 2 (R)] + (eg, R═CH 3 and CH 2 CH 3 ) by decarboxylation of [UO 2 (O 2 C─R)] + precursors and (b) to identify the pathways by which the complexes, if formed, dissociate by collisional activation or otherwise react when exposed to gas-phase H 2 O. Collision-induced dissociation (CID) of both [UO 2 (O 2 C─CH 3 )] + and [UO 2 (O 2 C─CH 2 CH 3 )] + causes H + transfer and elimination of a ketene to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…This was demonstrated by van Stipdonk et al, who noted that UO 2 2+ acetates fragment differently depending on the polarity of the complex: ketene elimination to form cationic UO 2 OH + or neutral ligand elimination to form an anionic UO 2 + acetate. 78,81 Because of the disparate cationic and anionic reactivity observed in the gas-phase, future studies that probe hydrolysis rates experimentally in [Ln III (CH 3 )-(Cl) 3 ] − and computationally in the cationic complexes of [Ln III (CH 3 )(CH 3 CO 2 )] + and [Ln III (CH 3 )(Cl)] + are encouraged.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was demonstrated by van Stipdonk et al, who noted that UO 2 2+ acetates fragment differently depending on the polarity of the complex: ketene elimination to form cationic UO 2 OH + or neutral ligand elimination to form an anionic UO 2 + acetate. 78,81 Because of the disparate cationic and anionic reactivity observed in the gas-phase, future studies that probe hydrolysis rates experimentally in [Ln III (CH 3 )-(Cl) 3 ] − and computationally in the cationic complexes of [Ln III (CH 3 )(CH 3 CO 2 )] + and [Ln III (CH 3 )(Cl)] + are encouraged.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…75,77,78,81,83 While reduction and decarboxylation are competitive for [Yb III (CH 3 CO 2 ) 4 ] − , reduction outcompetes decarboxylation for [Eu III (CH 3 CO 2 ) 4 ] − , and we are unable to isolate the trivalent organoeuropium complex. However, [Eu III (OH)-(CH 3 CO 2 ) 3 ] − is observable as a minor product, which could result either from an extremely fast hydrolysis with k hyd ′(EuIII ) > 2000 s −1 [unlikely in view of the other much slower k hyd ′(Ln III )] or via a ketene (CH 2 CO) elimination as a direct fragmentation product.…”
mentioning
confidence: 94%
“…Recent studies have reduced the levels of background H 2 O by employing a 2‐D linear ion trap, revealing reactions not seen with the previous instrument. After collisional activation under lower pressures of H 2 O, the [U VI O 2 (ClO 4 )] + ion forms the [U VI O 2 (Cl)] + ion, which will react over time with background H 2 O to form the familiar [U VI O 2 (OH)] + ion(Tatosian et al, 2019). This indicated that the original study observed a two‐step reaction, obscured by the high background levels of H 2 O in the 3‐D ion trap.…”
Section: Reactions Of Uranyl Complexesmentioning
confidence: 99%
“…Many oxygen‐containing organic ligands were studied by the van Stipdonk group. The uranyl propiolate ion, [UO 2 (O 2 C‐C = CH)] + , was subject to two rounds of CID, resulting in decarboxylation and the elimination of CO to yield the [OUCH] + ion (Tatosian et al, 2019). The product is a uranium‐methylidyne ion with a U ≡ C triple bond which reacts readily with O 2 upon collisional activation to form the UO 2 + ion.…”
Section: Reactions Of Uranyl Complexesmentioning
confidence: 99%
See 1 more Smart Citation